Epistemological Structure of Sufi Interpretation Pieter Coppens' Perspective - Khotijah, Siti; Rohmaniyah, Inayah (Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
This paper explores Pieter Coppens' construction of Sufi interpretation epistemology that dismantles the old knowledge of Sufi interpretation. The general conception of Sufi interpretation lies in the subjectivity of the interpreter. The mystical experience of divinity expressed in the interpretation is said to make the resulting interpretation invalid. However, this opinion is not accompanied by a deepening of Sufism elements in the Qur'an as something interpreted. Less comprehensive studies compartmentalize and tend to authorize the legality of an interpretation. This paper will be elaborated through three questions, namely how the elements of Sufism in the Qur'an according to Coppens, the epistemological structure, and its implications for interpretation. This research is literature research with qualitative method. The results of this study indicate that Sufi interpretation is like any other interpretation, due to its dogmatic and conservative nature. Because of his opinion, he presents the Sufi mufasir's opinion that never comes out of his theological beliefs, and always uses the opinions of previous interpreters to strengthen his interpretation. According to Coppens, a tafsir is considered a 'Sufi' tafsir if it refers to terms such as 'figurative' (ishāra), 'revealing' (kasyf), and 'inward' (bāṭin) to describe its method of interpretation. In addition, Sufi tafsir is also based on visionary experiences that are experimental and mystical in nature.